New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula - Delgado-Blas, Víctor Hugo; Díaz-Díaz, Óscar; Viéitez, José M. (Zootaxa, 2018)
Re-assessment of spionid specimens from Iberian Peninsula initially assigned to Dispio uncinata Hartman, 1951 and Streblospio benedicti Webster, 1879 led to the recognition of two new species from the spionid genera Dispio and Streblospio from coasts around the Iberian Peninsula. Dispio elegans sp. nov. is characterised by having an oblanceolate-shaped prostomium. In addition, the first two notopodial postchaetal lamellae are serrated with digitiform papillae, the anterior neuropodial lamellae are smooth; all branchiae are almost completely fused to the notopodial lamellae, but with the tips free; the notochaetae on chaetiger 1 are smooth, alimbate capillaries; the ventral chaetae located in the position of the sabre chaetae on chaetigers 1–2 are smooth, alimbate capillaries, but becoming granulated on chaetiger 3; and the middle and posterior chaetigers are granulated and reticulated. Streblospio padventralis sp. nov. is characterized by lacking dorsal papillae between the branchiae of chaetiger 1; the hooks have 4–5 pairs of small teeth; sabre chaetae are present from chaetiger 3; the pygidium has two ventral lappets; and brooding structures are present in the coelomic cavities. We suggest raising the status of Streblospio benedicti japonica Imajima, 1990 to full species level as S. japonica Imajima, 1990. A key for Streblospio species is provided.